Insulin oedema and treatment‐induced neuropathy occurring in a 20‐year‐old patient with Type 1 diabetes commenced on an insulin pump. Issue 1 (12th December 2013) - Rothacker, K. M.; Kaye, J.
Abstract Background Oedema may occur following initiation or intensification of insulin therapy in patients with Type 1 and Type 2 diabetes. Mild oedema is thought to be not uncommon, but under‐reported, whilst generalized oedema with involvement of serous cavities has rarely been described. Multiple pathogenic mechanisms have been proposed, including insulin‐induced sodium and water retention. Patients at greater risk for insulin oedema include those with poor glycaemic control. Dramatic improvement in glycaemic control is also associated with sensory and autonomic neuropathy. Case report We describe a case of generalized oedema occurring in a 20‐year‐old, low body weight patient with Type 1 diabetes with poor glycaemic control 3 days following commencement of an insulin pump; blood sugars had dramatically improved with this treatment. Alternative causes for oedema were excluded. Oedema slowly improved with insulin dose reduction with higher blood sugar targets plus frusemide treatment. Subsequent to oedema resolution, the patient unfortunately developed generalized neuropathic pain, thought to be another manifestation of rapid improvement in glycaemic control. Conclusion Caution should be taken when a patient with diabetes that is poorly controlled has an escalation in therapy that may dramatically improve their blood sugar levels; this includes the initiation of an insulin pump. Clinicians and patients should be aware of the potential risk of insulin oedema, treatment‐induced neuropathy and worsening of diabetic retinopathy in the setting of rapid improvement in glycaemic control.